2015
DOI: 10.5935/1806-0013.20150036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact on quality of life of patients with temporomandibular disorders

Abstract: BACKGROUND AND OBJECTIVES: Chronic pain, such as temporomandibular disorder, often leads to significant changes in quality of life. This study aimed at evaluating the influence of temporomandibular disorders in the subjective perception of quality of life by means of the Oral Health Impact Profile-14. METHODS:Participated in the study 80 patients diagnosed with temporomandibular disorders by means of the Research Diagnostic Criteria for Temporomandibular Disorders, aged between 18 and 60 years (32.71±1.1), who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
0
5
0
7
Order By: Relevance
“…In a study by Choi et al (2009) about pain disability on orofacial pain patients, chewing function was found to be one of the most interfered oral functions in orofacial pain patients [21] amongst other interfered oral functions. Other previous studies [22,23] also reported interfered physical oral functions including chewing function due to orofacial 6 Pain Research and Treatment pain or temporomandibular disorders that was accompanied by pain, which in turn has decreased the patients' quality of life. In a study conducted by De Laat et al (2003) about the impact of different course of therapy on myofascial pain of the masticatory system patients, a decreased pain score after four to six weeks of therapy was revealed, accompanied by a decreased Mandibular Function Impairment Questionnaire (MFIQ) score, indicating that the pain reduction has improved patients' oral function [24].…”
Section: Discussionmentioning
confidence: 91%
“…In a study by Choi et al (2009) about pain disability on orofacial pain patients, chewing function was found to be one of the most interfered oral functions in orofacial pain patients [21] amongst other interfered oral functions. Other previous studies [22,23] also reported interfered physical oral functions including chewing function due to orofacial 6 Pain Research and Treatment pain or temporomandibular disorders that was accompanied by pain, which in turn has decreased the patients' quality of life. In a study conducted by De Laat et al (2003) about the impact of different course of therapy on myofascial pain of the masticatory system patients, a decreased pain score after four to six weeks of therapy was revealed, accompanied by a decreased Mandibular Function Impairment Questionnaire (MFIQ) score, indicating that the pain reduction has improved patients' oral function [24].…”
Section: Discussionmentioning
confidence: 91%
“…In a study by Choi et al (2009) about pain disability on orofacial pain patients, chewing function was found to be one of the most interfered oral functions in orofacial pain patients [ 21 ] amongst other interfered oral functions. Other previous studies [ 22 , 23 ] also reported interfered physical oral functions including chewing function due to orofacial pain or temporomandibular disorders that was accompanied by pain, which in turn has decreased the patients' quality of life. In a study conducted by De Laat et al (2003) about the impact of different course of therapy on myofascial pain of the masticatory system patients, a decreased pain score after four to six weeks of therapy was revealed, accompanied by a decreased Mandibular Function Impairment Questionnaire (MFIQ) score, indicating that the pain reduction has improved patients' oral function [ 24 ].…”
Section: Discussionmentioning
confidence: 94%
“…Dentre os principais fatores associados que podem influenciar na qualidade de vida dos pacientes pode-se destacar a presença de dor de cabeça e orofacial que também foi observada nos indivíduos (BACK et al, 2019), associação de fatores emocionais como depressão e ansiedade (NATU et al, 2018, PAULINO et al, 2018 e limitação funcional (RODRIGUES et al, 2015). A esse respeito Pigozzi et al, (2019) concluiu que a intensidade e disfunção da dor causada pela DTM apresentaram impacto negativo na qualidade de vida geral da saúde da população nos domínios físico, psicológico, social e ambiental.…”
Section: Discussionunclassified
“…Dentro os trabalhos analisados Pinto et al, (2015) em sua pesquisa concluiu que os aspectos dor e vitalidade influenciaram de forma negativa o estado geral de saúde dos indivíduos, no entanto, este impacto não os impede de realizar suas atividades de vida diária, e as atividades sociais não foram afetadas por seu estado físico, vale destacar que o grupo analisado era de estudantes de fisioterapia, o que talvez possa levar a essas pessoas a desenvolverem melhor essas atividades. Rodrigues et al, (2015) atenta para que o aumento da idade, a gravidade e a associação de diagnósticos exacerbaram o impacto da disfunção temporomandibular na qualidade de vida dos indivíduos, isso se torna essencial para um acompanhamento e análise mais detalhada dos pacientes e destes fatores associados.…”
Section: Discussionunclassified